Microwave-Enhanced Cross-Coupling Reactions Involving Alkynyltrifluoroborates with Aryl Bromides - George W. Kabalka; Abhijit Naravane; Vitali Coltuclu; Eric Dadush (Molecules, 2013)
Palladium-catalyzed alkynylation has emerged as one of the most reliable methods for the synthesis of alkynes which are often used in natural product syntheses and material science. An efficient method for coupling alkynyltrifluoroborates with various aryl bromides in the presence of a palladium catalyst has been developed using microwave irradiation. The microwave reactions are rapid and efficient.